Uneven distribution of zinc in the dorsal and ventral sections of rice grain - Pennapa Jaksomsak (2018)
This study examined the distribution of zinc in dorsal and ventral grain sections of rice varieties with low (RD21), moderate (CNT1 and KDML105), and high (KPK and NR) zinc concentrations. Samples of unhusked rice grain were partitioned longitudinally and analyzed for zinc. The concentration of zinc was higher in the dorsal grain section than the ventral section, but to a different extent in different varieties. In unpolished rice, the zinc concentration in the dorsal section exceeded that in the ventral section by 14% in CNT1 to 63% in RD21. The higher zinc concentration in the dorsal section of unpolished rice might be explained by storage in the multiple cell layered aleurone and thicker pericarp. The higher concentration of dorsal zinc, however, was maintained after polishing, irrespective of the removal of grain surface by polishing that varied with variety and polishing time from 11 to 207 μm in depth. Zinc concentration of polished rice, ranging from 14 to 28 mg of zinc/kg, was strongly predicted by the zinc in unpolished rice (P < 0.01). This uneven distribution of zinc in the dorsal and ventral sections of rice grain suggests a specific pattern by which zinc is laid down. Whether the region of endosperm and aleurone proximal to the dorsal vascular bundle may have a greater concentration of zinc transporters and zinc storage structures than in more distal areas is yet to be investigated. Understanding this distribution may aid efforts in zinc biofortification and evaluation of rice varieties for other nutritive characteristics. © 2014 AACC International, Inc.